Ninth Plan Sub Group Draft Report on Natural Gas Availability, Utilization and Distribution - Planning Commission (Planning Commission, 1996)
In line with the recommendation of Eighth plan. GAIL has taken up work on setting up new gas based LPG plant at Gandhar. User Lakwa and Auraiya These plants are expected to be commissioned during the Ninth Plan period and would significantly increase the production of LPG and associated products from processing of gas. The position regarding promotion of CNG in the transport sector is separately covered in detail in subsequent chapter The Bombay City Gas Distribution Project is already under implementation by the Joint Venture of GAIL and British Gas and the coverage would be significantly expanded during the Ninth Plan period The work is also likely to start on City Gas Distribution Project for Delhi, Agra and Ferozabad.
Planning Commission